2018
DOI: 10.5005/jp-journals-10024-2217
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Retrospective Study based on Implant Success Rate in Patients with Risk Factor: 15-year Follow-up

Abstract: Aim:The purpose of this retrospective study is to assess implant success rates with various risk factors. Materials and methods:Two hundred patients with a total of 650 implants were selected. Risk factors, such as smoking, antidepressants, bruxism, diabetes, and bone augmentation procedures were considered, and patients were followed up for a period of 8 to 15 years. Results:Of 650 implants placed, the success rate was 88%, i.e., a total of 572 implants were successful. A total of 78 implants were considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Risk factors such as diabetes, periodontitis, bruxism, smoking, antidepressants intake, bone augmentation procedures, head and neck radiotherapy [19][20][21][22] play a principal role in long-term implants' outcome. These factors are found at the patient level, meaning that they are poorly controllable over time, as they can worsen along with local or systemic health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors such as diabetes, periodontitis, bruxism, smoking, antidepressants intake, bone augmentation procedures, head and neck radiotherapy [19][20][21][22] play a principal role in long-term implants' outcome. These factors are found at the patient level, meaning that they are poorly controllable over time, as they can worsen along with local or systemic health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these publications showed this especially in poorly controlled diabetes mellitus with an HbA1c > 8% with increased probing depths, bleeding on probing and peri-implant bone resorption [ 19 , 45 ]. In five studies, no clear conclusion could be drawn from the data obtained, so that the question of an increased risk was not answered [ 10 , 25 , 33 , 43 , 64 ]. However, the available aggregated literature consistently concluded that diabetes mellitus represents a risk factor for the development of peri-implant inflammation, although most studies point to a lack of high-quality and long-term studies on this research area [ 8 , 50 , 51 , 54 56 , 58 , 60 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Kandasamy et al , risk factors for failure of dental implants include smoking, bruxism, diabetes, and bone augmentation. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%